Narratives of Twitter as a Platform for Professional Development, Innovation, and Advocacy. (August 2017) - Geia, Lynore; Pearson, Luke; Sweet, Melissa
Abstract : Objective: To explore why and how Twitter engagement may be useful for health professionals with an interest in decolonising practice and for supporting the social and emotional wellbeing (SEWB) of Aboriginal and Torres Strait Islander people. Method: A narrative methodology is used to explore innovative uses of Twitter with relevance to the SEWB of Aboriginal and Torres Strait Islander people. The authors present their personal and professional stories of engagement with Twitter as three inter‐related case studies. Results: Thematic analysis of these narratives found that Twitter is enabling Aboriginal and Torres Strait Islander people to share their stories and experiences, and to develop new connections and collaborations for change. It provides a platform for reflexivity, reciprocity, relationship‐building, strengths‐based learning and practice, advocacy, and other elements of decolonising practice. Conclusion: Engaging with Twitter offers psychologists and other health professionals an opportunity for improving their understanding of the complexity of factors affecting the SEWB of Aboriginal and Torres Strait Islander people, and for developing their professional practice into new spheres.